Controlling nematodes biologically - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Root-knot nematodes (Meloidogyne spp.) are major pests of a range of crops in tropical and sub-tropical climates. The high cost of nematicides has precluded their use in subsistence agriculture, and management of root-knot nematodes has relied on...